Pengolahan Limbah Padat Organik Berbasis Sosialisasi dan Aplikasi Teknologi Drum Komposter di Pondok Pesantren Nurul Islam Jember. - Firda Lutfiatul Fitria; Tika Kumala Sari; Noven Pramitasari; Alyaa Nur Karimah; Aulia Rachmawati Khumairo; Helma Agustin; Faishal Bagas Prakosa; Reza Dwi Saputra (Abdibaraya, 2026)
This community service activity was conducted at the Nurul Islam Islamic Boarding School [L2.1] in Jember, with the aim of increasing administrators' and students' awareness and ability to manage organic and liquid waste sustainably. The main problems partners face are limited knowledge of organic solid waste management, the lack of waste sorting, and the lack of appropriate technology to process organic waste into useful products. The methods used in this activity include socialization, training, demonstrations, and mentoring in the application of composter technology to process organic solid waste generated from Islamic boarding school activities. The results of the activity showed an increase in knowledge and awareness of partners as demonstrated through the results of the pretest and posttest, as well as changes in behavior in waste management. The implementation of a simple composter reduced the volume of organic waste and produced compost. Overall, this community service activity had a positive impact on the Islamic boarding school's environmental, social, and educational aspects. This program is expected to be sustainable and further developed, and replicated in other locations with similar problems.